Social Network Analysis: User Responses to Lazada Marketplace Promotions: Analisis Jaringan Sosial: Respon Pengguna terhadap Promosi di Lazada Marketplace - Meynur Rohmah Ubaidillah; Rita Ambarwati Sukmono (Universitas Muhammadiyah Sidoarjo, 2023)
This study employs qualitative research methods to measure and map user interactions with marketing promotional content on Lazada Marketplace, focusing on images related to vouchers, cashback offers, and flash sales. Data was collected from Twitter and analyzed using Wordij and Gephi to filter and process the data. Social Network Analysis (SNA) with Crawling Data was applied to determine user responses. The findings reveal the patterns of user interactions within the Lazada Marketplace, specifically in relation to vouchers, cashbacks, and flash sales. Furthermore, the study identifies the user response trends between 2018-2019 and 2020-2021, highlighting the marketing promotional content that received the most and least responses. Notably, the results indicate a significant user response to